Potentially Dangerous Spiders - Pellitteri, Phil; Lewis, Donald; Hahn, Jeffrey D. (St. Paul, MN: University of Minnesota Extension Service, 1997)
Explains the benefits of spiders in nature, and cautions against spider bites. Identifies some spiders known to cause severe bites.
2 pages.
This archival publication may not reflect current scientific knowledge or recommendations. Current information available from the University of Minnesota Extension: https://www.extension.umn.edu.
Keywords: Araneae; bites and stings